(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
A human being continues to have his dignity, self-respectand HRs even while under any form of detention or imprisonment. He should notbe subjected to torture, cruel or degrading treatment or punishment. Even thosefacing death penalty have their basic rights.[1] [1]. With a view to promoting and protecting the HRs of prisoners,the UN has prescribed the following standards for the treatment of prisoners:(a) Body of Principles for the Protection of all Persons under any form ofDetention or Imprisonment (General Assembly resolution 43/173 of 9 Dec. 1988,adopted without vote); (b) Standard Minimum Rules for the Treatment ofPrisoners (adopted by the first UN Congress on the Prevention of Crime and theTreatment of Offenders, held at Geneva in 1955, and approved by the ECOSOC byits resolutions 663 C (XXIV) of 31 July 1957 and 2076 (LXII) of 13 May 1977);and (c) Safeguards Guaranteeing Protection of the Rights of Those Facing theDeath Penalty (Approved by ECOSOC resolution 50 of 25 May, 1984). Besides, theCAT lays out the steps to prevent torture and other cruel inhuman or degradingtreatment or punishment of prisoners.